(untitled) (Tempo e Argumento, 2022)
The article analyses the participation of Black Unified Movement into the Amnesty struggles against torture, disappearances and violence’s committed by the state agents during and after the military dictatorship. It is argued that racial abuse against minorities and particularly the black people, were not considered as human rights violation by the amnesty law and transitional justice politics. Even though the democratization politics recognized the fallacy of the ideology of racial democracy, it maintained the juridical system and the repressive law that allows the practices of torture and violation of basic human rights by state agents. The fact that only a specific group of white and middleclass political activist were recognized as victims of State violence, constrained the possibility of collective acknowledgement not only of recent past wrongdoing, but also the open historical wounds left by the slavery and colonial heritage, which is argued to be part of the necessary ethical-political transformation of the Brazilian history. It brings also that the state apologies initiatives have instrumentalized the victim’s feelings reinforcing the vulnerability and the truth of the losers.